From Asia to Aigina: the story of the pistachio tree - Chitzanidis A. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
For a long time the origin of the tree was obscure. At the end of the 19th century De Candolle, Boissier, Engler and other botanists considered Syria, Turkey and Mesopotamia to be the home of P. vera and this is still written in horticultural books. In 1929-1930, though, Russian botanists (Popov, Morozoff and others) who visited Central Asia discovered P. vera growing wild in huge stretches of mountains and plains, forming savanna like park forests in semi arid environments. The data from West Asia were no doubt taken from cultivated trees. The area of wild P. vera extends from Northern Iran, Northern Afghanistan, Southern Turkmenistan, East Uzbekistan, Tajikistan, Kyrgyzstan (Zohary, 1950-1952). This indicates that Central Asia is the home of the wild progenitor of this nut. But the presence of P. vera in Central Asia was noticed also earlier by other visitors of the area. In 1841 a traveller A. Lemann wrote in his memoirs that in a march he made on the mountains of Tajikistan, near the border of Uzbekistan, he walked for 50 verst (55 kilometers) mostly through pistachio forests (Bretzl, 1903).The pistachio tree (Pistacia vera L.) in Greece, P. vera is connected with the island of Aegina. It is the main crop on the island, the nut is called Aeginian pistachio to distinguish it from the peanut which is called in Greece Arabian pistachio and the Greek female cultivar of the tree is called Aigina.In the decades of 1950 and 1960 the cultivation of pistachios expanded all over the country from south to north and on the islands. Aegina is no longer the main pistachio producing area of Greece but historically it remains the area from which the pistachio production has started.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)